Analisis Usaha Ternak Sapi Po, Domba Lokal, dan Kambing EtawaPada Kelompok Peternak Peternakan Mandiri Jaya, Desa Balingbing, Pagaden Barat: Agribusiness Analysis of Cattle Po, Local Sheep, and Etawa Goats in The Mandiri Jaya Livestock Farmer Group, Balingbing Village, West Pagaden - Fathia, Siti Diana; Asmara, Andi; Nurdiansyah, Dian Hakip (Fakultas Peternakan Universitas Jambi, 2024)
Background: Livestock business is a potential business to be developed in rural and suburban areas in developing countries such as Indonesia, but there are still many farmers who do not really understand the Business Analysis and the profit obtained from their own livestock. Purpose: This study aims to determine the livestock raising activities at the Mandiri Jaya Livestock Farmer Group in Balingbing Village, West Pagaden Subdistrict and analyze the business of cattle, sheep and goats. Methods: The data collection method carried out is by following the activity process and interviews to obtain primary data, while secondary data is obtained by conducting literature studies, reading from various book sources, the internet, and print or electronic media. Results: The results of field work practices carried out on cattle (PO), sheep (Local), and goats (Etawa) in the Mandiri Jaya Livestock Farmer Group are, total investment costs of Rp. 156,738,000, total variable costs of Rp. 157,764,000, total fixed costs of Rp. 680,000, total revenue of Rp. 211,900,000, and get a net profit of Rp. 53,456,000, and get a B / C Ratio value of 0.34, R / C Ratio of 1.34 and ROI of 34%. Conclusion:It can be concluded that the business is profitable seen from the amount of R / C Ratio of more than 1, which is 1.34, which means that the R / C Ratio> 1, so the cattle, sheep and goat business in the Mandiri Jaya Livestock Farmer Group is profitable and feasible to develop.